Developing VILLE 5.0 (Virtual Language Laboratory based on Education 5.0) as an Innovative Learning Model - Transinata, Tatas; Riana, Rati; Situmorang, Adolf (Universitas Cokroaminoto Palopo, 2023)
Learning English in the Education 5.0 era encourages massive changes, especially in the learning models and media. Researchers developed an Innovative learning model that plays a very important role, namely VILLE 5.0 (Virtual Language Laboratory based on Education 5.0). The subjects in this research were 93 students of the 11th grade Vocational High School SMK Perdana Semarang. The instruments used questionnaires and expert validation tests. Data was processed by analyzing validator response data with a Likert scale. The syntax VILLE 5.0 learning model consist of providing the problem, making the group, doing inquiry through virtual media, constructing the media, simulating the solution, and presenting the result on virtual media. The results of VILLE 5.0 validity test are very valid level, while the feasibility aspects from students’ view were 96% and from the teachers’ view were 92 %. The score for practicality test were 95% from the teachers and 92% score from the students. The conclusion based on the results that VILLE 5.0 are valid, feasible and practical. VILLE 5.0 can be used as an innovative learning model for English Subject. VILLE 5.0 is very comprehensive to be implemented as an Education 5.0 learning model era because the class can optimize the technology and